Hemoglobin Concentration May Affect the Effect of Atorvastin on Chronic Subdural Hematoma After Burr-Hole Drainage at High Altitude - Wei, Linjie; Lin, Chi; Zhong, Mingfeng; Zhang, Jianbo; Zhu, Gang (Frontiers in Neuroscience, 2020)
Objective Chronic subdural hematoma (CSDH) is a common disease. Atorvastatin calcium can increase CSDH absorption. However, whether atorvastatin can increase hematoma absorption and reduce recurrence at high altitudes is not clear. Methods After burr-hole drainage, CSDH patients were divided into an atorvastatin group and a control group. Follow-up computed tomography (CT) was performed on day 1, months 1, 2, and 3 after surgery. Then, the recurrence rate, poor therapeutic effect, time to recurrence, poor surgical result, recurrence with operation, CSDH volume, and Markwalder grading scale score (MGSS) were calculated, and related risk factors were analyzed. Results The non-recurrent and recurrent patients in the control group differed significantly in terms of the hemoglobin concentration (HB) [176.24 ± 16.43 vs. 194.25 ± 12.34 (g/L), p < 0.01], CT value [41.92 ± 10.76 vs. 34.12 ± 8.78 (Hu), p < 0.01], and low-density time [3.88 ± 1.04 vs. 5.50 ± 0.87 (d), p < 0.01]. The non-recurrent and recurrent patients in the atorvastatin group differed significantly in terms of the HB [172.66 ± 16.41 vs. 190.45 ± 10.23 (g/L), p < 0.01], CT value [38.91 ± 7.16 vs. 29.50 ± 8.61 (Hu), p < 0.01], and mixed [2 vs. 4 (n), p < 0.05] and low-density time [4.09 ± 0.75 vs. 5.45 ± 1.12 (d), p < 0.01]. The logistic regression analysis showed that HB [odds ratio, 1.14; 95% confidence interval (CI), 1.04–1.25 in the control group, odds ratio, 1.13; 95% CI, 1.03–1.23 in the atorvastatin group] and low-density time (odds ratio, 3.53; 95% CI, 1.42–8.74 in the control group, odds ratio, 2.53; 95% CI, 1.10–5.80 in the atorvastatin group) were possible risk factors for the two groups. The receiver operating characteristic curves showed that the area under the receiver operating characteristic curve values for the HB, CT value (Hu), and low-density time were 0.812, 0.702, and 0.755 for all subjects; 0.812, 0.719, and 0.790 for the control group; and 0.807, 0.682, and 0.756 for the atorvastatin group, respectively. The postoperative follow-up results showed that there was no significant difference in the recurrence rate, poor therapeutic effect, time to recurrence, poor surgical result, recurrence with operation, CSDH volume, or MGSS between the two groups. Conclusion The effect of atorvastatin was not significant after the operation. The risk factors for CSDH recurrence were the HB and low-density time. The HB was the most specific and sensitive predictor of CSDH recurrence.